I Am The Light Of This World - Parker, Michael, 1959- (Chapel Hill, North Carolina : Algonquin Books of Chapel Hill, 2022)
"The story of Earl, a 17-year-old boy who goes to prison for a crime he didn't commit"--.
new book 2023 winter.
Keywords: Teenage boys; Ex-convicts; Judicial error; Novels